Magnetic carbon nanotubes grafted with smart polymer brushes for highly efficient enantioseparation of tryptophan enantiomers. Issue 47 (25th November 2019) - Yang, Xiao-Rong; Lei, Li; Peng, Zhuo; Yu, Hai-Rong; Cheng, Chang-Jing
Abstract : We herein report a novel chiral carbon nanotube nanomaterial (MCNTs–PNG–CD) grafted with smart copolymer brushes for highly efficient chiral recognition and separation of tryptophan enantiomers (dl -Trp). Abstract : We herein report a novel type of chiral carbon nanotube nanomaterial (MCNTs–PNG–CD) based on smart polymer brush grafted magnetic carbon nanotubes (MCNTs) for highly efficient chiral recognition and separation of tryptophan enantiomers (dl -Trp). The grafted PNG–CD smart polymer brushes are composed of thermosensitive poly( N -isopropyl acrylamide- co -glycidyl methacrylate) (PNG) copolymer chains with numerous appended beta-cyclodextrin (β-CD) units, which play a crucial role in efficient chiral discrimination and separation of dl -Trp. PNG–CD was fabricated on Fe3 O4 nanoparticle-loaded carbon nanotubes (CNTs) by combining surface-initiated atom transfer radical polymerization (SI-ATRP) with a ring opening reaction. MCNTs–PNG–CD was systematically characterized by transmission electron microscopy (TEM), Fourier transform infrared (FT-IR) and Raman spectroscopy, thermogravimetric analysis (TGA), vibrating sample magnetometry (VSM) and elemental analysis (EA). The prepared MCNTs–PNG–CD demonstrates highly thermosensitive chiral recognition and enantioselectivity toward dl -Trp, which is based on host–guest interactions between β-CD units and l -tryptophan (l -Trp) and the thermosensitive volume phase transition of poly( N -isopropylacrylamide) (PNIPAM) chains. The operating temperature and initial concentrations of AAs are two significant factors that affect the chiral recognition and separation of dl -Trp. Furthermore, the obtained MCNTs–PNG–CD also exhibits satisfactory reusability and excellent magnetic separability from enantiomeric solutions. Such a multifunctional CNT nanomaterial can serve as a high-performance nanoselector for direct enantioseparation of various chiral compounds.